Applicability on Static-Dynamic Verification Method for Seismic Design of Steel Tubular Bridge Piers with Cruciform Plates - Wang Zhanfei; Sui Weining; Toshitaka Yamao; Liang Yongqiang (International Journal of Architectural Engineering Technology, 2016)
Steel tubular bridge pier with inner cruciform plates has high seismic performance. In this paper, the applicability of static-dynamic verification method for seismic design of steel tubular bridge piers with inner cruciform plates is studied. The ultimate strength and state of steel tubular stub columns with inner cruciform plate subjected to compression and bending were investigated through finite element analysis. The validity of the proposed design formula of the failure strain which was obtained from the stub column analysis was examined by analysis on tubular steel bridge piers with inner cruciform plates under cyclic loading. The dynamic response analysis of the same steel bridge piers was carried out on the basis of the spring-mass model and the fiber element model. These results indicated the static-dynamic verification method of the seismic response analysis through the spring-mass model are good agreement with dynamic verification method of seismic response analysis by the fiber element model.